2014
DOI: 10.1227/neu.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

The Severity of Basilar Invagination and Atlantoaxial Dislocation Correlates With Sagittal Joint Inclination, Coronal Joint Inclination, and Craniocervical Tilt

Abstract: This study has demonstrated for the first time the important role of joint orientation and its correlation with the severity of BI and AAD and has described new joint indexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 30 publications
4
43
2
Order By: Relevance
“…In the plain radiographs era, Smoker et al[19] had demonstrated that this angle changed about 30 o from flexion to extension neck position, also reporting that normal range varied from 150° to 180°. Our limited variation from flexion to extension compared to the reported by Chandra et al[11] may be explained by the fact that some of our patients had clivus hypoplasia and atlas assimilation which may decrease CVJ motion when compared with normal subjects. Platybasia may lead to a lower CCA and CVJ kyphosis, with brainstem symptoms as well as compensatory subaxial hyperlordosis.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In the plain radiographs era, Smoker et al[19] had demonstrated that this angle changed about 30 o from flexion to extension neck position, also reporting that normal range varied from 150° to 180°. Our limited variation from flexion to extension compared to the reported by Chandra et al[11] may be explained by the fact that some of our patients had clivus hypoplasia and atlas assimilation which may decrease CVJ motion when compared with normal subjects. Platybasia may lead to a lower CCA and CVJ kyphosis, with brainstem symptoms as well as compensatory subaxial hyperlordosis.…”
Section: Discussioncontrasting
confidence: 55%
“…Symptomatic congenital CVJ malformation: Chiari Malformation (CM), characterized by tonsillar herniation through the foramen magnum or BI with or without CM who underwent posterior fossa decompression; age > 15 years old (younger patients have incomplete ossification of the region and were excluded)[11]; a complete sagittal CT scan of the CVJ in flexion and in extension (a head holder was used to flex the neck and a pad roll was placed below the shoulders for the extended position); non evident AAD or facet subluxation on static radiological exams.…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggest that reciprocal interaction may likely affect not only global balance but also regional balance. 33 Another interesting finding is that neck flexion, and extension movement is initiated primarily by motions between the head and C1. 34 As the head approaches full flexion and extension, contributions from the upper cervical segments decrease, whereas the lower cervical segments' contribution increases.…”
Section: A B Cmentioning
confidence: 97%
“…In patients with IrAAD, the C1-2 joints were oblique, both in sagittal and coronal planes. The joint orientation can be quantified using technique described by Chandra et al 1 or Salunke et al 23 We chose the latter method. The joints were relatively normal or slightly oblique in patients with RAAD.…”
Section: Radiological Differencesmentioning
confidence: 99%